Changes in China's Iron Ore Import Pattern in the Context of COVID-19 - Xiao Renrong; Zhao Pengjun; Xiao Ting; Gao Yichun; Yang Juan (Redai dili)
China imports more than 80% of its iron via sea. The spatiotemporal patterns of iron ore shipping, as well as its changes, are linked to the China's national economic security. The COVID-19 pandemic has profoundly affected the spatiotemporal patterns of global shipping. By studying the changing trend of China's iron ore import pattern during the pandemic, this study attempts to provide a basis and experience to prevent similar crises and improve supply chain resilience in the future. This study employs Automatic Identification System data to estimate China's iron ore imports during the COVID-19 pandemic from January to June 2020. Furthermore, this study integrates the standard deviation ellipse and origin-destination, flow analysis methods to examine changes in the iron ore trade pattern. The findings reveal the following. 1) The import pattern of iron ore in China exhibits pronounced geographical concentration. In terms of port distribution, the Bohai Rim serves as a core hub, hosting the majority of the country's major ore-receiving ports. Among them, the Caofeidian Port, Zhoushan Port, and Jinggang Port constitute three strategic fulcrums. 2) From the perspective of trade source countries, China's iron ore imports face substantial market concentration risks. Australia (accounting for over 60%) and Brazil (accounting for over 20%) contributed more than 80% of the total import volume, forming a highly dependent supply system. The main ports for iron ore exports from Australia are located on the west coast, including Ports Hedland, Dampier, and Walcott, while Port Itaqui in Brazil is also a major source of China's iron ore imports. 3) COVID-19 had the greatest impact on China's iron ore imports in February 2020. Imports rebounded in March as production resumed in China. In May, a higher import share in the Yangtze and Pearl River Delta regions shifted the import center slightly southward, although it remained along the southern boundary of the Bohai Rim port cluster. Despite the pandemic, the Bohai Rim ports retained their status as the primary import hubs. 4) Compared with 2019, iron ore exports from major exporters, including Australia, Brazil, South Africa, India, and Ukraine, increased from January to June 2020. China's dependence on iron ore from Australia and Brazil has decreased annually, while its dependence on Ukraine and India has increased. This has led to a westward shift in overseas iron ore supply centers. 5) Among ports with a monthly throughput exceeding 5 million tons, the iron ore supply to China from Australia's Ports Hedland, Dampier, and Walcott generally increased, whereas Brazilian Itaqui Port experienced a continuous decline in its supply to China starting in February. Among significant ports with a monthly throughput below 5 million tons, Peru's San Nicolas Port and South Africa's Saldanha Bay Port were the most severely impacted by the pandemic, with a notable reduction in their iron ore supply to China.